2021
DOI: 10.1155/2021/8106467
|View full text |Cite
|
Sign up to set email alerts
|

Cloud-Based Fault Prediction Using IoT in Office Automation for Improvisation of Health of Employees

Abstract: The novel paradigm of Internet of Things (IoT) is gaining recognition in the numerous scenarios promoting the pervasive presence of smart things around us through its application in various areas of society, which includes transportation, healthcare, industries, and agriculture. One more such application is in the smart office to monitor the health of devices via machine learning (ML) that makes the equipment more efficient by allowing real-time monitoring of their health. It guarantees indoor comfort as per t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…(a) Social Connect of Individuals. People are socially so deeply connected that they cannot restrict meeting their near and dears, be it in a residential society, a township, a village [45]. (b) Attending the Di erently Abled Ones.…”
Section: Social Bindingsmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) Social Connect of Individuals. People are socially so deeply connected that they cannot restrict meeting their near and dears, be it in a residential society, a township, a village [45]. (b) Attending the Di erently Abled Ones.…”
Section: Social Bindingsmentioning
confidence: 99%
“…ere have been administrative e orts to make people isolated, but on ground, things have not been executed as planned. It has been observed that huge gatherings have taken place irrespective of any number of daily positivity rates in one or the other part of the world [46].…”
Section: Devotional and Religiousmentioning
confidence: 99%
“…Biological big data: High-throughput sequencing technology is rapidly evolving, increasing the data output capability of life-science-related research organisations, resulting in a variety of gaps across the spectrum of genomics, transcriptomics, proteomics, and metabolomics research, among others [32,33]. The enormous value of these biological data serves to successfully encourage the advancement of biological research, which has applications in agriculture, health, and medicine, among other fields of endeavour [34].…”
Section: Big Data In Health Carementioning
confidence: 99%
“…For example, real-time data can be provided by Internet of Things solutions, and large data flows are managed and secured by robust digital infrastructures. In addition, flows and decision-making support are improved by command centers, artificial intelligence, and machine learning [10][11][12]. However, it is through the creation of DTs that much of this can be brought together [8].…”
Section: Introductionmentioning
confidence: 99%